Pastureland use of China: Accounting variations from different input-output analyses. (October 2021) - Li, Chaohui; Wu, Xudong; Chen, Guoqian; Han, Mengyao; Chen, Kuang; Yangzong, Ciren; Lo, Dan; Alsaedi, Ahmed; Hayat, Tasawar
Abstract: This paper conducts a systematic accounting on the use of China's pastureland in the world economy by using systems embodiment analysis. This study is in direct association with a pioneering paper "Embodied pasture land use change in China 2000–2015: from the perspective of globalization" (Guo et al., 2019). Both the previous and the present work explore China's case of pastureland use from an embodiment perspective by using systems input-output analysis. However, diﬀerent results and policy implications were produced. The previous study concluded that China has paid a high price for sacriﬁcing its pastureland resources to foreign regions since it is a net exporter of pastureland resources, and protection policies are urgently needed to reduce such export ﬂow. The results from the present study, on the other hand, show that China is a major importer of pastureland use throughout 2000–2015, and that only 9.51% of China's exploited pastureland resources are embodied in international trade, leaving around 90.79% of China's pastureland resources at home to satisfy domestic demand. This paper shows the setting of system boundary and the input-output table used in calculations can determine not only the magnitude of hidden resource use in supply chains but also the direction of resource use flow hidden in international trade. We conclude by raising policy implications based on the present study, and call for uniformity of methods to improve robustness of assessments on trade-related land use studies. Highlights: China is a net importer of embodied pastureland use. China's pastureland demand is mainly displaced to Mongolia, Australia, and the United States. Foreign demand drive around one-tenth of China's domestic pastureland exploitation. Analysis from SRIO and MRIO produce opposite results regarding trade flow directions. Homogenous production intensity assumption may produce biased virtual import amount by 47−252%.